Georgia : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
The centerpiece of the program is fiscal consolidation, to put Georgia on a path to fiscal sustainability, establish the ability of the government to meet its commitments, and underpin efforts to resolve the large external debt burden. Expenditure restraint should be complemented by reforms to increase fiscal transparency and strengthen expenditure monitoring and control. Maintaining low inflation and a stable exchange rate is required. Combating corruption and improving governance will be the key to attracting the investment needed to ensure strong, sustainable growth and poverty reduction.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet